A Case Study Using Chirabilva as a Single Drug Remedy to Manage Kitibha Kushta - Sidaraddi, Vinoda Y; Sri, Mamatha (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Kitibha is a skin disease, explained in Ayurveda under the broad term kushta. It is characterized by shyava, kinakharasparsha, parusha, and khandu. It can be correlated with psoriasis based on clinical features. Psoriasis is a proliferative autoimmune skin disease. About 2-3% of the population have psoriasis according to the World Psoriasis Day Consortium. Materials and Methods: Chirabilva Kashaya internally and Chirabilva Taila externally were advised for the patient diagnosed as Kitibha Kushta for 30 days and assessment done before treatment, after treatment, and after follow-up. Discussion: The drug Chirabilva having the Kustahara, Lekhaniya, Bhedaniya, and Krimihara properties was selected for the treatment of Kitibha Kushta and it was administered both internally and externally in kashaya and taila form, respectively, to study the effectiveness of single drug in Kitibha Kushta of recent origin. Conclusion: Chirabilva as a single drug when given internally and externally relieved the symptoms, so in acute cases even without panchakarma single drug can be effective in managing the disease.